Liver transplant and impact on cerebral autoregulation: a systematic scoping review - Rochat, Tommaso; Ulaj, Artida; Sangla, Frederic; De Stefano, Pia; Quintard, Herve (Frontiers in Transplantation, 2026)
BackgroundCerebral autoregulation (CA)—the brain's ability to maintain stable cerebral blood flow (CBF) despite changes in mean arterial pressure (MAP)—may be disrupted during orthotopic liver transplantation (OLT) due to profound metabolic, inflammatory, and hemodynamic alterations. Such impairment could increase the risk of cerebral hypoperfusion or hyperemia, yet its perioperative evolution and clinical implications remain unclear. This systematic scoping review aimed to synthesize current evidence on CA monitoring during OLT and to identify methodological gaps and potential clinical applications.MethodsA systematic scoping review was conducted according to Joanna Briggs Institute (JBI) guidelines. Studies including adult patients undergoing OLT with quantitative perioperative CA assessment were identified across PubMed, Embase, Scopus, Web of Science, and Medline.ResultsSix studies (n = 99) met inclusion criteria. CA was assessed using diverse methods, including transcranial Doppler (TCD), near-infrared spectroscopy (NIRS), and derived indices such as the pressure reactivity index (PRx), mean flow index (Mx), cerebral oximetry index (COx), static cerebral autoregulation index (SCAI), and transfer function analysis (TFA). Monitoring phases and definitions of impaired CA varied widely. In acute liver failure, CA was commonly impaired pre-transplant and improved postoperatively, whereas findings in chronic liver disease were inconsistent. Only a few studies explored associations with neurological outcomes, yielding inconclusive results.ConclusionsCA appears to be dynamically affected during OLT, particularly in acute liver failure, but evidence remains limited by methodological heterogeneity and small sample sizes. Standardized, prospective studies are needed to clarify the role of CA monitoring and to determine whether individualized blood pressure management could improve neurological outcomes.